2008
DOI: 10.1002/ar.20715
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Microcirculation in Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD), the most common cause of steatosis, is associated with visceral obesity and insulin resistance. With more severe risk factors (obesity, type 2 diabetes [T2D], metabolic syndrome), steatosis may be complicated by hepatocellular injury and liver inflammation (steatohepatitis or NASH). NASH can lead to perisinusoidal fibrosis and cirrhosis. Fat-laden hepatocytes are swollen, and in steatohepatitis, further swelling occurs due to hydropic change (ballooning) of hepatocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(201 citation statements)
references
References 71 publications
9
186
2
4
Order By: Relevance
“…PTX leads to increased tissue perfusion and improved regional microcirculation and tissue oxygenation. PTX improves liver npg perfusion in humans [30,31] . PTX may therefore lessen the acute hepatic injury induced by a high-fat diet and may be partially associated with increased hepatic arterial blood flow and alleviation of early hepatic circulatory disturbances in rats with NASH.…”
Section: Discussionmentioning
confidence: 98%
“…PTX leads to increased tissue perfusion and improved regional microcirculation and tissue oxygenation. PTX improves liver npg perfusion in humans [30,31] . PTX may therefore lessen the acute hepatic injury induced by a high-fat diet and may be partially associated with increased hepatic arterial blood flow and alleviation of early hepatic circulatory disturbances in rats with NASH.…”
Section: Discussionmentioning
confidence: 98%
“…NAFLD is associated with hepatic sinusoid microcirculation (Farrell et al 2008). Liver sinusoidal endothelial cells (LSECs) play important roles in regulating hepatic sinus function.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in sinusoidal flow and sinusoidal narrowing have been described. 8,9 We recently reported that portal pressure is significantly elevated in severe NAFLD in a rat model. 10 This indicates an important increase of the intrahepatic resistance with haemodynamic repercussions in severe steatosis.…”
mentioning
confidence: 99%